Civil Servant Performance: Study on the Koperasi Daya Karya, Sintang District Education and Culture Office - Eka Apriyani; Annisa Rizqa Alamri; Syarifah Nurma Afhiani; Ahirul Habib Padilah; Dwi Nur Handayani (Universitas Muhammadiyah Gorontalo, 2022)
This paper aims to show how the performance of the Koperasi Daya Karya in the Sintang District Office of Education and Culture has so far been. Using a qualitative descriptive method, this study describes several problems that refer to the first aspect of responsiveness, namely the ability to identify the needs of members, prioritize services, develop agendas, and develop service programs for members who have not been running optimally and not yet optimal. unfulfilled needs and aspirations of members; secondly, the responsibility for implementing activities at “Daya Karya” has not been carried out with administrative principles that are in line with cooperative policies, the level of conformity between the formulation of the vision and mission of the Koperasi and the dynamics of change, the level of anticipation in dealing with change; accountability of